APPLICATIONS OF SURFACE SENSITIVE TECHNIQUES IN THE STUDY OF PHOTOCHEMICAL PROCESSING AT THE SOLID-GAS INTERFACE. - Jackman, R; Foord, J (Les Editions de Physique, 1986)
The applications of surface sensitive techniques to chemical problems arising in photochemical processing are considered. Both their use in ex situ and in situ modes are described. Results for three photochemical processes are presented dealing with the chemical origins of periodic ripples in LCVD deposits, W metallisation from WF//6 vapour and photo-enhanced etching.